A novel conditional gene silencing method using a tumor-specific and heat-inducible siRNA system. (1st June 2016) - Feng, Jing; Wang, Xiaoyu; Liao, Yi; Feng, Jianguo; Tang, Liling
Abstract: RNAi technology is an invaluable tool for investigating gene function. However, the non-temporal and non-spatial control is the primary limitation, which leads to siRNA leakiness and off-target effects. In this study, we inserted three kinds of HSE into tumor specific promoter hTERT, which aims to construct a temperature-inducible and tumor-specific RNAi plasmid vector. In our system, the expression of mature siRNA is tightly controlled by the heat shock-inducible and tumor-specific promoters. From the expression level of RNA and protein, we determined the efficiency of the inducible siRNA system by targeting SNCG gene in HepG2 and MCF-7 cells. Results showed that the controllable siRNA system could be induced to initiate siRNA expression by heat-induce. The silencing effect of SNCG is on a relative low level (10 %) at 37 °C, while it is significantly increased to 50 or 60 % after heat inducing at 43 °C. This new conditional siRNA system provides a novel approach to drive the siRNA expression by heat-inducible and tumor-specific promoter.